One Question at a Time, Please! - Spruce, Chris (Maine Policy Review, 1996)
In the Margaret Chase Smith Essay, Chris Spruce addresses the conundrum of public referenda, championed by many as the most direct form of democracy and criticized by others for creating winners and losers without the traditional give and take of American politics. He reviews the recent history of public referenda in Maine, including the recent clear-cutting initiative. Perhaps we lose more than we gain when we oversimplify complex public issues with inherently conflicting values biases.
Keywords: Maine; referendum initiatives; clearcutting